2012
DOI: 10.1007/s11695-012-0839-1
|View full text |Cite|
|
Sign up to set email alerts
|

Surgical Weight Loss: Impact on Energy Expenditure

Abstract: Diet-induced weight loss is often limited in its magnitude and often of short duration, followed by weight regain. On the contrary, bariatric surgery now commonly used in the treatment of severe obesity favors large and sustained weight loss, with resolution or improvement of most obesity-associated comorbidities. The mechanisms of sustained weight loss are not well understood. Whether changes in the various components of energy expenditure favor weight maintenance after bariatric surgery is unclear. While the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 87 publications
1
35
0
1
Order By: Relevance
“…A recent review indicated that total energy expenditure in humans often decreases due to the decrease in fat-free and fat mass but that diet-induced thermogenesis is often increased (please see also below) (145). Nonetheless, some studies in humans report an increase in total energy expenditure, similar to the data in rodents.…”
Section: Energy Expenditurementioning
confidence: 86%
See 2 more Smart Citations
“…A recent review indicated that total energy expenditure in humans often decreases due to the decrease in fat-free and fat mass but that diet-induced thermogenesis is often increased (please see also below) (145). Nonetheless, some studies in humans report an increase in total energy expenditure, similar to the data in rodents.…”
Section: Energy Expenditurementioning
confidence: 86%
“…The majority of data collected with the help of preclinical studies seems to be consistent with findings in humans. However, changes in energy expenditure after RYGB seem to be less consistent in humans compared with most animal models, but this may be related to the much larger heterogeneity of study populations in humans compared with laboratory animals (23,31,145,146,152).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, fat tissue as a metabolically active body component contributes to REE as well, as demonstrated by Das et al (21) . Various studies have been carried out so far to compare the effect of different bariatric procedures on resting energy expenditure and body composition (30) . To our knowledge, no randomized study compared sleeve gastrectomy to the gastric bypass procedure in terms of REE by means of indirect calorimetry.…”
Section: Prior To This Study Only Moizé Et Al Had Compared Changes Inmentioning
confidence: 99%
“…1,2 Nevertheless, the evaluation of results after bariatric surgery continues to be debated, as the variation in weight loss is hard to explain. 3 Moreover, weight regain after surgery is a recurrent element in long-term (410-year) follow-up studies. 4 Failure rates of up to 35% have been reported with respect to expected weight loss over time.…”
Section: Introductionmentioning
confidence: 99%